The Relationship Between Teachers’ Perception of the Head Teacher’s Leadership Style and Teachers’ Job Satisfaction at an International School in Bangkok - Dampier, Stephen; Banks, Jerome (Scholar: Human Sciences, 2019)
The purpose of this study was to examine the relationship between the teachers’ perception of the Head Teacher’s leadership style and the teachers’ job satisfaction at a selected International School in Bangkok, Thailand. The researcher conducted a quantitative study to answer the research questions and test the research hypothesis; there is a significant relationship between the teachers’ perception of the Head Teacher’s leadership style and job satisfaction. The results indicated the teachers’ did not perceive the Head Teacher to use a transformational leadership style. The teachers showed they were neither satisfied nor dissatisfied. Finally, the analysis indicated that there was no significant relationship between the teachers’ perception of the Head Teacher’s leadership style and their level of job satisfaction. The researcher recommended that the Head Teacher should act more as a mentor or a coach to the teaching staff. Also a more collaborative culture should be fostered amongst staff.